2008
DOI: 10.1183/09031936.00112407
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adiposity measured by dual-energy X-ray absorptiometry on lung function

Abstract: Respiratory function is impaired in obesity but there are limitations with body mass index and skin-fold thickness in assessing this effect. The present authors hypothesised that the regional distribution of body fat and lean mass, as measured by dual-energy X-ray absorptiometry (DXA), might be more informative than conventional measurements of total body fat.In total, 107 subjects (55 female, 51.4%) aged 20-50 yrs with no respiratory disease were recruited. Respiratory function tests, anthropometric measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
103
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 20 publications
10
103
1
7
Order By: Relevance
“…Gender differences have also been noted in adults. Recent studies in asthmatic and nonasthmatic adults have reported similar positive associations between lean mass and respiratory function in males only (16,17), whereas negative associations between lean mass and lung function have been reported in female adults with asthma (17).…”
Section: Body Composition and Lung Functionmentioning
confidence: 91%
See 3 more Smart Citations
“…Gender differences have also been noted in adults. Recent studies in asthmatic and nonasthmatic adults have reported similar positive associations between lean mass and respiratory function in males only (16,17), whereas negative associations between lean mass and lung function have been reported in female adults with asthma (17).…”
Section: Body Composition and Lung Functionmentioning
confidence: 91%
“…Previous studies have indicated that the regional distribution of body composition may be important to respiratory function in asthmatic and nonasthmatic adults (15)(16)(17) and nonasthmatic children (18). In adults, total and regional fat mass have been negatively associated with dynamic and static lung function, with more evident differences in associations between males and females (16,17).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…This is explained by the adaptation to chronic overload that accompanies obesity. Wannamethee et al 21 and Sutherland et al 22 reported that the increase in respiratory muscle strength is due to the increase in lean mass, hence the importance of the presence of body mass in the predictive equations, particularly for assessing respiratory muscle strength in morbid obesity.…”
Section: Discussionmentioning
confidence: 99%